Morphological and molecular characterization of tick species infesting cattle in South Africa - Makwarela, T.G.; Nyangiwe, N.; Masebe, T.M.; Djikeng, Appolinaire; Nesengani, L.T.; Smith, R.M.; Mapholi, N.O. (MDPI, 2024)
Ticks are a significant threat to livestock globally, with certain species displaying distinct host preferences at various developmental stages. Accurate species-level identification is essential for studying tick populations, implementing control strategies, and understanding disease dynamics. This study evaluated ticks infesting cattle across six provinces in South Africa using morphological and molecular methods. Ticks were preserved, examined morphologically using an Olympus Digital Camera Microscope, and identified using the 16S rRNA gene. The study identified four genera, namely Amblyomma, Hyalomma, Ixodes, and Rhipicephalus, comprising 15 ixodid species. Amblyomma hebraeum was the most prevalent species, with an infestation rate of 54.4%. Molecular analysis revealed genetic relationships among tick species, with genetic distances ranging from 0.00 to 0.13, and phylogenetic analysis clustered species into distinct genera with high bootstrap support. Principal Component Analysis highlighted clear genetic relatedness among species. These findings enhance our understanding of tick diversity, morphology, and distribution in South Africa’s cattle populations, emphasizing their economic significance. The study provides critical baseline data for monitoring and developing effective strategies to manage tick-borne diseases, ensuring improved livestock health and productivity.